Runaway inflation; experiences and options - Felipe Pazos (CEPAL Review, 1990)
Inflation was a major concern for Prebisch from his time in central banking np to the end of his career, when he stressed the need for new thinking by Latin American economists about stabilization policy. The topic is of vital importance, not only for Latin America, but also for the world in general, for specialists in industrialized countries have also been unable to elaborate policy recommendations for their governments that will resolve the dilemma between inflation and monetary restriction.